2012
DOI: 10.1089/acm.2011.0392
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Establishing an Integrative Medicine Primary Care Clinic in Sydney, Australia

Abstract: Although many integrative medicine clinics fail to survive the first few years, after 4 years, this multidisciplinary primary care clinic had succeeded in establishing a viable health care service offering both integrative medicine and conventional, traditional, complementary, and alternative medicine. Finding the right mix of staff members and following up with evaluations to track progress are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…8 Convergent beliefs regarding professionalism and philosophy are essential components within the integrative medicine setting. 10,13,18 Sharing a common philosophy that is aligned with beliefs and values surrounding primary health care delivery concedes trust in the other practitioners' professionalism and ability. This is an especially important concept for IM clinics, where medicolegal and ethical responsibilities are paramount in each practitioner's mind.…”
Section: Discussionmentioning
confidence: 99%
“…8 Convergent beliefs regarding professionalism and philosophy are essential components within the integrative medicine setting. 10,13,18 Sharing a common philosophy that is aligned with beliefs and values surrounding primary health care delivery concedes trust in the other practitioners' professionalism and ability. This is an especially important concept for IM clinics, where medicolegal and ethical responsibilities are paramount in each practitioner's mind.…”
Section: Discussionmentioning
confidence: 99%
“…Management observed that the business model of the clinic required at least half the practitioners to be biomedical doctors. 24 One reason given was that the biomedical doctors were an important referral source for the less busy TCAM and allied-health practitioners. Comments from the staff questionnaire suggested that referrals within the clinic were mostly between the biomedical doctors and the TCAM and allied-health practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Patient preferences played a significant role in the development of the clinic. 24 The directors and practitioners in the clinic trialed different IM services such as implementing specialty health programs in which a group of practitioners worked together as an integrated team and offered joint consultations with more than one practitioner. However, there was little patient demand for these integrated health care services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations